2019
DOI: 10.1074/jbc.ra118.006128
|View full text |Cite
|
Sign up to set email alerts
|

Converter domain mutations in myosin alter structural kinetics and motor function

Abstract: Edited by Karen G. Fleming Myosins are molecular motors that use a conserved ATPase cycle to generate force. We investigated two mutations in the converter domain of myosin V (R712G and F750L) to examine how altering specific structural transitions in the motor ATPase cycle can impair myosin mechanochemistry. The corresponding mutations in the human ␤-cardiac myosin gene are associated with hypertrophic and dilated cardiomyopathy, respectively. Despite similar steady-state actin-activated ATPase and unloade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 68 publications
(84 reference statements)
1
26
0
Order By: Relevance
“…One major factor that may account for the differences in ATP hydrolysis is the light chain content. Interactions between the converter domain and essential light chain have been demonstrated (27,28), and myosins that vary only by the light chain content were found to have different ATP hydrolysis rate constants (29,30). Interestingly, the light chain content of the C2C12 cell expressed/purified myosin could vary depending on how long the cells are differentiated before harvest (e.g.…”
Section: Impact Of Dilated Cardiomyopathy Mutant In Cardiac Myosinmentioning
confidence: 99%
See 1 more Smart Citation
“…One major factor that may account for the differences in ATP hydrolysis is the light chain content. Interactions between the converter domain and essential light chain have been demonstrated (27,28), and myosins that vary only by the light chain content were found to have different ATP hydrolysis rate constants (29,30). Interestingly, the light chain content of the C2C12 cell expressed/purified myosin could vary depending on how long the cells are differentiated before harvest (e.g.…”
Section: Impact Of Dilated Cardiomyopathy Mutant In Cardiac Myosinmentioning
confidence: 99%
“…Palmer et al (41) observed that cardiac muscle from heterozygous F764L knockout mice exhibited significantly reduced cross-bridge stiffness, and therefore proposed that the F764L leads to a more compliant converter domain and myosin cross-bridge. Our recent work investigated the force-generating properties of the corresponding mutation (F750L) in myosin V, and found that this mutant is less able to overcome frictional loads compared with WT in the loaded in vitro motility assay (30). The F750L mutation also alters the recovery stroke rate constant and shifts the equilibrium between conformational states of the lever arm in several nucleotide states.…”
Section: Impact Of F764l On M2␤mentioning
confidence: 99%
“…Although most of the compounds in the present study have been used to treat non-contractile dysfunction in humans (as anti-cancer, anti-psychotic, and anti-malarial agents), it is possible that some of them, or derivatives of them, have therapeutic potential for cardiomyopathy where attenuation of contractility is beneficial, as in a hypercontractile state caused by HCM mutations in myosin or actin (38,39). Regulation of striated muscle contractility is not only thin-filament dependent, but also thick-filament dependent, whereby the myosin binding affinity to actin is attenuated via phosphorylation of the light chains (40) and myosin-binding protein C (41,42), changes in flexibility and conformation (LC domain (43), converter region (44), actin binding region (3,45), and small molecules (Mava and OM) (39) that affect the myosin ATPase cycle. In the present study, we have shown that the compounds increase ATP affinity and decrease the rate constant for the subsequent isomerization steps in ternary complex formation (and hence the release of S1 from actin), which is likely to produce actin-bound non-force producing heads, resulting in decreased ATPase activity.…”
Section: Potential Therapeutic Applicationsmentioning
confidence: 99%
“…Pivotal to this allosteric communication is the central seven-stranded β-sheet (the transducer) (twisted in the rigor state, but untwisted in the pre-power stroke state) in the myosin motor domain, which couples the large actin-binding cleft (closed while strongly attached to F-actin, and open in actin-detached states) with the active site phosphate-sensing elements—the P-loop, switch-1 and switch-2—(closed in the hydrolysis-competent pre-power stroke state, but partially or fully opened in all other states) as well as through the relay helix (bent in the pre-power stroke state, while straight in the rigor state) and SH1/SH2-region with the mechanical converter and lever arm (down position in the rigor state, and up position in the pre-power stroke state). We and others have shown that mutations in these key regions disturb the motor function by interfering with chemomechanical coupling pathways [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%